2016
DOI: 10.1186/s12888-016-0805-x
|View full text |Cite
|
Sign up to set email alerts
|

Variation and ethnic inequalities in treatment of common mental disorders before, during and after pregnancy: combined analysis of routine and research data in the Born in Bradford cohort

Abstract: BackgroundCommon mental disorders (CMD) such as anxiety and depression during the maternal period can cause significant morbidity to the mother in addition to disrupting biological, attachment and parenting processes that affect child development. Pharmacological treatment is a first-line option for moderate to severe episodes. Many women prescribed pharmacological treatments cease them during pregnancy but it is unclear to what extent non-pharmacological options are offered as replacement. There are also conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 50 publications
0
39
0
Order By: Relevance
“…24 Three studies reported on data from GP patient records; one examined 411 entries in GP records, 29 and another two papers reported data from GP records of 8991 and 2234 women from the same cohort. 34,35 Where several types of health-care professionals were surveyed, results are reported from GPs and FPs only. Three papers reported on care during pregnancy, 25,33,35 five papers focused on the postpartum period, 28,29,31,32,36 and five studied both pregnancy and the postpartum period.…”
Section: Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…24 Three studies reported on data from GP patient records; one examined 411 entries in GP records, 29 and another two papers reported data from GP records of 8991 and 2234 women from the same cohort. 34,35 Where several types of health-care professionals were surveyed, results are reported from GPs and FPs only. Three papers reported on care during pregnancy, 25,33,35 five papers focused on the postpartum period, 28,29,31,32,36 and five studied both pregnancy and the postpartum period.…”
Section: Studiesmentioning
confidence: 99%
“…34,35 Where several types of health-care professionals were surveyed, results are reported from GPs and FPs only. Three papers reported on care during pregnancy, 25,33,35 five papers focused on the postpartum period, 28,29,31,32,36 and five studied both pregnancy and the postpartum period. 24,26,27,30,35 Ten papers used a questionnaire or survey to gather information from participants, of which four papers also included a vignette.…”
Section: Studiesmentioning
confidence: 99%
See 3 more Smart Citations